The great British rake-off: How the government has misled Parliament and the British people on public sector pensions - Neil Record (Institute of Economic Affairs (IEA), 2021)
The government is misleading Parliament and the public over the cost to the taxpayer of public sector pensions. This takes the form of the government reporting its pensions cost in a different way from that required by pension regulations in the private sector.I estimate the unreported annual cost at 57 billion in 2020-21, or approximately 30% of the public sector payroll.
Keywords: 330